Elaboration and Characterization of SnO2 Doped TiO2 Gas Sensors Deposited through Dip and Spin Coating Methods - Zineb Essalhi (Proceedings, 2019)
Semiconductor functional materials play an increasingly important role in science and technology because of their unique optical, electrical, magnetic, catalytic and chemical properties. They are widely used in fields such as solar cell, photo-catalysts, optical coating, capacitors for large scale integrated devices, electrochromic systems and gas sensors. One important application for semiconductor gas sensors is the detection of pollutant gases for the control of the combustion process.